21. ASSOCIATION BETWEEN MIDAZOLAM AND POSTOPERATIVE COGNITIVE DYSFUNCTION IN ELDERLY PATIENTS FOLLOWING JOINT ARTHROPLASTY (Vietnam Journal of Community Medicine, 2024)
Background: Postoperative cognitive dysfunction greatly affects the quality of recovery aftersurgery, especially in the elderly, prolonging hospital stay. To reduce anxiety and stress for patientswho are anesthetized with spinal anesthesia using sedation. Therefore, we hypothesized that the useof midazolam sedation during surgery is related to postoperative cognitive dysfunction in elderlypatients following joint arthroplasty.Objective: Determine the relationship between midazolam and cognitive disorders after jointreplacement surgery in the elderly.Materials and Methods: Elderly patients (≥ 60 years) receiving spinal anesthesia for jointarthroplasty. Design of this study is longitudinal observational, prospective, single-center.Results: 22,5% of elderly patients had postoperative cognitive dysfunction for joint arthroplasty andreceived spinal anesthesia in the first 5 days of surgery. Elderly patients with postoperative cognitivedysfunction have a longer postoperative treatment (p < 0.05). Multivariable Cox regression analysisnoted that using of sedative midazolam during surgery (p=0,002) was a risk factor for postoperativecognitive dysfunction.Conclusions: Of all the 107 patients, we noted that elderly patients with postoperative cognitivedysfunction have a longer postoperative treatment. The use of sedative midazolam during surgery isa risk factor for postoperative cognitive dysfunction.
Keywords: Postoperative cognitive dysfunction, elderly people.